The nurse in the prevention of antineoplastic agents extravasation: a literature review - Vieira, Milena do Nascimento (2021)
The extravasation of antineoplastic agents consists of the infiltration of the anticancer agent in the extracellular space and surrounding tissues, due to the administration of the drug outside the blood vessel, which can cause severe reactions in the tissue. It is essential to prevent this event, providing the patient with a safe and secure treatment. effective, as well as the non-incidence of damage. This study aimed to identify, in scientific productions, preventive measures against the extravasation of antineoplastic agents, and to analyze the main recommended nursing care. This is an integrative review using LILACS, PUBMED and BDENF databases to search for studies. Among the preventions associated with the extravasation of antineoplastic agents, the most prevalent nursing care was the need to train the nursing staff, the establishment of institutional protocols and guidelines, constant monitoring of the perforated site, puncture of large veins and calipers in the forearm and the use of a small caliber catheter. Thus, it is considered that extravasation events may be associated with a lack of training and scientific and technical knowledge of the nursing team, adequate nursing care can prevent this event and promote safe hospitalization, being essential the performance of the nursing team, applying quality care to prevent this scenario.